THERMOGRAVIMETRIC INVESTIGATIONS OF VAGINAL SUPPOSITORY WITH THYME OIL - N. V. Melnikova; V. V. Gladishev; B. S. Burlaka (Zaporozhye State Medical University, 2015)
One of the main stages in new medicines creation is the development of their making technology. Technological process of suppository making includes ratherlongthermal treatment during preparation and homogenization of suppository base, active substancesaddition. These factors create danger of chemical and physical transformation of active substances and excipients in suppository up to their destruction and change of pharmacological and physical-chemical properties. Use of thermogravimetric analysis in pharmaceutical technology allows to studythepossibility of chemical interaction in dosage forms over the wide temperature range. The aim of this work is study of thermal treatmenteffects of suppository base with thyme oil over the temperature range of suppository manufacturing. Methods and results. As an object of thermogravimetric study vaginal suppository with thyme oil 0,2 g, suppository-placebo containing propylenglycol, polyethylene glycol 400, proxanol 268, twin 80 and the active ingredient of «Царствоароматов», Ukraine, production were used. Thermogravimetric analysis was carried out on the derivatograph«Shimadzu DTG-60», Japan, with the platinum and platinum-rhodiumthermopair with samples heating in aluminiumcrucibles from 25 to 200ºС. As standard α-Al2O3was used.Heating rate was 10ºСper min.Mass of the samples was 23,45- 39,63 mg. Obtained data were registered by the derivatograph as curves T, DTA, TGA. The T curve on the derivatogramm shows the temperature change and the TGA curve demonstrates the sample mass change during investigation. The DTA curve reflects differentiation of thermal effects and contains information about endothermic and exothermal maximum and is used for qualitative valuation of derivatogramm. According to results of thermogravimetric investigation the thyme oil is thermostable substance which is gradually evaporating during heating. So, at the beginning of study the test sample mass was 23,45 mg at 26,14º С, then the thyme oil mass has been decreased on 1,41% at 50,2º С and on 4,14% at 69,48 ºСaccordingly. In accordance with results of thermogravimetric study of suppository with thyme oil and placebo vaginal dosage form (base) it was revealed that both objects of investigation don't reach the critical temperature within 100ºС. That fact isindicated by the insignificant mass loss (3,35% and 3,44%accordingly). Derivatography of compositions upper 100ºС wasn't carried out because such high temperatures aren't used in technological process of suppository manufacturing. Melting process of suppository base is going at 53,41°С. Addition of thyme oil in suppository base insignificantly decrease melting temperature of composition to 51,25°С, moreover the mass loss of sample is practically absent (0,04%). Conclusion. Character of the thermal effects of vaginal suppository with thyme oil on the derivatogrammcoincides with the thermal effects of suppository base. This fact indicates the absence of any chemical interactions between active substance and excipients of application dosage form.